Monomorphic epitheliotropic intestinal T-cell lymphoma comprises morphologic and genomic heterogeneity impacting outcome - Veloza, Luis; Cavalieri, Doriane; Missiaglia, Edoardo; Ledoux-Pilon, Albane; Bisig, Bettina; Pereira, Bruno; Bonnet, Christophe; Poullot, Elsa; Quintanilla-Martinez, Leticia; Dubois, Romain; Llamas-Gutierrez, Francisco; Bossard, Céline; et al. (Haematologica (Roma), 2023)
Monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL) is a rare aggressive T-cell lymphoma most reported in Asia. We performed a comprehensive clinical, pathological and genomic study of 71 European MEITL patients (36 males, 35 females, median age 67 years). The majority presented with gastrointestinal involvement and had emergency surgery, and 40% had stage IV disease. The tumors were morphologically classified into two groups: typical (58%) and atypical (i.e., non-monomorphic or with necrosis, angiotropism or starry-sky pattern) (42%), sharing a homogeneous immunophenotypic profile (CD3+ [98%] CD4- [94%] CD5- [97%] CD7+ [97%] CD8+ [90%] CD56+ [86%] CD103+ [80%] cytotoxic marker+ [98%]) with more frequent expression of TCRgd (50%) than TCRab (32%). MYC expression (30% of cases) partly reflecting MYC gene locus alterations, correlated with non-monomorphic cytology. Almost all cases (97%) harbored deleterious mutation(s) and/or deletion of the SETD2 gene and 90% had defective H3K36 trimethylation. Other frequently mutated genes were STAT5B (57%), JAK3 (50%), TP53 (35%), JAK1 (12.5%), BCOR and ATM (11%). Both TP53 mutations and MYC expression correlated with atypical morphology. The median overall survival (OS) of 63 patients (43/63 only received chemotherapy after initial surgery) was 7.8 months. Multivariate analysis found a strong negative impact on outcome of MYC expression, TP53 mutation, STAT5B mutation and poor performance status while aberrant B-cell marker expression (20% of cases) correlated with better survival. In conclusion, MEITL is an aggressive disease with resistance to conventional therapy, predominantly characterized by driver gene alterations deregulating histone methylation and JAK/STAT signaling and encompasses genetic and morphologic variants associated with very high clinical risk.